Kotak Kosong dalam Perspektif Hak Memilih dan Dipilih pada Pilkada Kabupaten Kebumen 2020 - Ika Aurelia Natasya; Fairuz Arta Abhipraya; Sakir Sakir (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2021)
The 2020 Kebumen Regional Election Contest was followed by a single candidate for the incumbent pair Arif Sugiyanto and Ristawati Purwaningsih. To choose between an empty box or a defense candidate pair, is something new, especially for the people of Kebumen Regency, however the presence of this phenomenon is different, presenting a different political spirit, but on the other hand it should put political decisions into an election method that does not require an option in order to reduce participation. society in a democracy. This writing aims to understand the causal scope of the empty boxes in the 2020 Pilkada of Kebumen Regency, which present single nominees and empty boxes. This research method is carried out by qualitative research methods using descriptive analysis techniques because in this study aims to reveal reality, and present the conditions and circumstances that occur. Data collection techniques are obtained by secondary data in the form of journal articles, news, and other library studies related to this research. The results of this study indicate that in the implementation systematics there is no complete fulfillment of rights that the pilkada followed by single candidate pairs and empty boxes is evidence of the implementation of democracy in accordance with a human rights perspective.